Ticarcillin degradation product thiophene acetic acid is a novel auxin analog that promotes organogenesis in tomato - George, Suja; Rafi, Mohammed; Aldarmaki, Maitha; ElSiddig, Mohamed; Nuaimi, Mariam Al; Sudalaimuthuasari, Naganeeswaran; Nath, Vishnu Sukumari; Mishra, Ajay Kumar; Hazzouri, Khaled Michel; Shah, Iltaf; Amiri, Khaled M. A. (Frontiers in Plant Science, 2023)
This article is currently in production. The final, formatted version of the article will be published soon.